EFFECTS OF FIXED AND RANDOM FACTORS ON BIRTH AND WEANING WEIGHT IN GUINEA PIGS OF THE CENTRAL COAST OF PERU - Rodríguez L., Humberto (2013)
The purposes of this study were a) to evaluate the effect of random factors such as litter (L) and fixed effects such as season (S), calf sex (CS), and parity (P) on birth weight (BW) and weaning weight (WW); and b) to estimate the phenotypic correlation between BW and WW. The study was conducted in the Cieneguilla guinea pig farm of the Universidad Nacional Agraria La Molina. The data comprised 5460 and 3514 records for BW and WW respectively of improved guinea pigs. The data was collected from January 2009 to July 2010. Weaning was at 14 days of age. The feeding system was based on broccoli crop residues (Brassica oleracea italica) and concentrate. SAS MIXED procedure (v 9.1) was used to analyze the mixed models. Total born (TB) was used as covariate for BW and born alive (BA) and age of weaning (AW) were used as covariate for WW. BW was influenced (p<0.01) by TB, S, CS and P, and WW was influenced (p<0.001) by BA, AW, S, P and P*S interaction. The phenotypic correlation of BW and WW was 0.64 (p<0.01). Litter variance was 54 and 60% of total variance for BW and WW respectively.